Infections of the Ears, Nose, Throat, and Sinuses (Springer International Publishing, 2018)
This text serves as a practical but comprehensive guide to diagnosing and treating ear, nose, throat, and sinus infections. The 30 chapters have been contributed by otolaryngologists and infectious disease specialists who are experts in the field. Topics include common infections such as otitis media, otitis externa, pharyngitis, laryngitis, and acute bacterial sinusitis, as well as less common infections such as mumps, scrofula, malignant otitis externa, Lemierre's syndrome, invasive fungal sinusitis, and deep neck infections. Human papillomavirus-related neoplasms, biofilms, chronic sinusitis, antibiotic-resistant infections, and measures to prevent surgical site infections are also discussed. Written with the practicing clinician in mind, Infections of the Ears, Nose, Throat, and Sinuses will be an invaluable aid to otolaryngologists, infectious disease specialists, internists, pediatricians, and primary care providers.